Progressive Scoliosis in a Child with Cystic Fibrosis - Lauren M. Castner; Samya Z. Nasr; Manuel Arteta (Case Reports in Pediatrics)
We discuss an adolescent female with cystic fibrosis, asthma, and scoliosis who had a rapid decline in her pulmonary function despite typical treatment for a cystic fibrosis exacerbation. Ultimately, she had a fixed airway obstruction likely due to her progressive scoliosis, which improved following surgical intervention.